Constitutional right to the Internet and digital governance in Georgia (Discourse of Law and Administration, 2023)
E-government uses information and telecommunication technologies to make public services available electronically to various stakeholders. It also aims to improve democratisation and leads to the construction of an information society. Such projects – aimed at modernising public administration activities are also undertaken in Georgia. The related issues of access to and use of the internet have been elevated to the status of one of the fundamental rights. Indeed, a provision establishing the right to access and use the internet was introduced in the Georgian Constitution in 2017. At the same time, a number of initiatives have been taken to support and develop e-government, such as the introduction of the possibility to use the electronic apostille clause or the implementation of numerous e-service portals. The benefits have undoubtedly been that the automation of processes has reduced the likelihood of ‘human error’ and the scope for the use of broad discretionary powers by public officials has become much narrower. In this context, the reduction of corruption and abuse by officials is undoubtedly one of the many benefits of the larger-scale implementation of digitalisation in Georgia.
Keywords: constitutional right to Internet; e-government in Georgia